Nonaqueous electrolyte additive for lithium secondary batteries, nonaqueous electrolyte for lithium secondary batteries containing the same, and lithium secondary battery

By using new compounds with a cyclic sulfur oxide structure as a nonaqueous electrolyte additive in lithium-ion batteries, a stable SEI layer is formed, which solves the problem of SEI layer collapse during high-temperature storage and improves the high-temperature storage and cycling performance of the battery.

JP7666810B2Active Publication Date: 2025-04-22LG CHEM LTD +1
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
JP2023521391
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2021-03-29
Filing Date
2022-03-28
Publication Date
2025-04-22
Estimated Expiration
2042-03-28

AI Technical Summary

Technical Problem

When existing lithium-ion batteries are stored at high temperatures, the solid electrolyte interface (SEI) layer gradually collapses, resulting in the negative electrode surface exposure, triggering side reactions and gas generation, increasing the internal pressure of the battery, and affecting battery performance.

Method used

A new compound with a cyclic sulfur oxide structure is used as a nonaqueous electrolyte additive, which is able to form a low impedance and stable SEI layer in the battery, preventing exposure and side reactions from the negative electrode surface.

Benefits of technology

By forming a stable SEI layer, the high-temperature storage and circulation performance of lithium-ion batteries is improved, gas generation and battery volume changes are reduced, and battery life is extended.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007666810000001
    Figure 0007666810000001
  • Figure 0007666810000002
    Figure 0007666810000002
  • Figure 0007666810000003
    Figure 0007666810000003
Patent Text Reader

Abstract

The present invention relates to a compound having a cyclic sulfur oxide structure, a non-aqueous electrolyte additive containing the compound, a non-aqueous electrolyte, and a lithium secondary battery. The lithium secondary battery of the present invention can achieve stable performance over a long period of time and can achieve improved effects in terms of high-temperature stability and gas generation.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] This application claims the benefit of priority based on Korean Patent Application No. 10-2021-0040213 filed on March 29, 2021, the entire contents of which are incorporated herein by reference.

[0002] The present invention relates to a compound that can provide excellent high-temperature cycle characteristics and high-temperature storage characteristics when used as an additive for a non-aqueous electrolyte, a non-aqueous electrolyte containing the compound, and a lithium secondary battery. [Background technology]

[0003] Lithium secondary batteries are energy storage devices that have been attracting the most attention in recent years because they can be made small and lightweight and can store high-density energy. Lithium secondary batteries are used in a wide variety of products, from small portable devices such as mobile phones and laptop computers to large devices such as electric vehicles, and since the environments and conditions in which each product is used are different, it is important to achieve stable performance regardless of the environment and conditions.

[0004] Meanwhile, a lithium secondary battery mainly includes a positive electrode, a negative electrode, a separator, and an electrolyte. The positive electrode is a source of lithium ions, and during charging, lithium ions from the positive electrode move to the negative electrode and are stored there, and during discharging, lithium ions stored in the negative electrode move to the positive electrode, releasing electrons to generate electrical energy. The electrolyte acts as a medium for the movement of lithium ions between the positive electrode and the negative electrode, and includes salt, a solvent, and an additive. The salt acts as a passageway for the movement of lithium ions, the solvent dissolves the salt well to assist the movement of lithium ions, and the additive is added to improve specific performance depending on the desired characteristics of the lithium secondary battery.

[0005] The additives can play various roles depending on the type, and one of the most typical roles is to form a solid electrolyte interface (SEI) on the surface of the electrode. In lithium secondary batteries, the positive electrode active material structurally collapses as charging and discharging proceeds, and metal ions eluted from the collapsed surface of the positive electrode are electrodeposited on the negative electrode, causing the performance of the positive electrode and the negative electrode to deteriorate. In this case, if an additive is added to the electrolyte, the additive is decomposed during the initial charging and discharging, and can form a coating called a solid electrolyte interface (SEI) on the surface of the electrode. The formed SEI can prevent performance deterioration when the charging and discharging cycle is repeated without hindering the movement of lithium ions, and can play a role in improving battery characteristics, storage characteristics, load characteristics, etc.

[0006] Specifically, the SEI film formed during the initial charge and discharge prevents the lithium ions from reacting with the carbon-based negative electrode or other materials during subsequent repeated charge and discharge, and serves as an ion tunnel that selectively allows only lithium ions to pass between the electrolyte and the negative electrode. Due to the ion tunnel effect, the SEI film prevents the organic solvent of the electrolyte, which has a large molecular weight, from moving to the carbon-based negative electrode, thereby preventing the carbon-based negative electrode structure from collapsing. That is, the formed SEI film suppresses side reactions between the lithium ions and the carbon-based negative electrode or other materials, so that the amount of lithium ions can be reversibly maintained during subsequent charge and discharge.

[0007] In other words, the carbon material of the negative electrode reacts with the electrolyte during initial charging to form a passivation layer on the surface of the negative electrode, preventing further decomposition of the electrolyte and maintaining stable charging and discharging. At this time, the charge consumed to form the passivation layer on the surface of the negative electrode is an irreversible capacity, and does not react reversibly during discharging. For this reason, lithium-ion batteries do not undergo any further irreversible reactions after the initial charging reaction, and can maintain a stable life cycle.

[0008] However, when a lithium-ion battery is stored at high temperature in a fully charged state (for example, after being charged 100% at 4.15 V or more and then stored at 60° C.), there is a problem that the SEI film gradually breaks down over time. Such a breakdown of the SEI film exposes the surface of the negative electrode, and the exposed surface of the negative electrode reacts with the carbonate-based solvent in the electrolyte and is decomposed, causing continuous side reactions. Furthermore, such side reactions continue to generate gas. The gas generated by the side reactions, regardless of the type, increases the internal pressure of the battery and acts as a resistance element in the movement of lithium, causing the thickness of the battery to expand and causing the performance of the battery to deteriorate.

[0009] Therefore, in order to provide a lithium secondary battery that can achieve stable and excellent performance, an additive is required that can form a stable and less decomposable SEI and that prevents the formed SEI from adversely affecting the performance of the electrode. [Prior art documents] [Patent documents]

[0010] [Patent Document 1] JP 2019-179638 A [Patent Document 2] JP 2018-156761 A Summary of the Invention [Problem to be solved by the invention]

[0011] The present invention aims to provide a compound having a cyclic sulfur oxide structure, which can realize excellent cycle characteristics of a lithium secondary battery and achieve improved effects in terms of high-temperature stability and gas generation, and a nonaqueous electrolyte additive containing the same.

[0012] Another object of the present invention is to provide a non-aqueous electrolyte solution containing the non-aqueous electrolyte additive, and a lithium secondary battery containing the non-aqueous electrolyte solution. [Means for solving the problem]

[0013] In order to solve the above problems, the present invention provides a novel compound, a non-aqueous electrolyte additive and a non-aqueous electrolyte containing the compound, and a lithium secondary battery containing the non-aqueous electrolyte.

[0014] (1) The present invention provides a compound represented by the following chemical formula 1:

[0015] [ka]

[0016] In the above Chemical Formula 1, n is 1 or 2; L 1 and L 2 are each independently a direct bond or a substituted or unsubstituted C1-C6 alkylene group, R 1 and R 2 are each independently a substituent represented by the following chemical formula 2, [ka] In the above Chemical Formula 2, m is 1 or 2; X 1 and X 2 are each independently -O- or -C(R 31 )(R 32 )-, wherein said X 1 and X 2 At least one of is -O-; R 31 ~R 36 are each independently a hydrogen atom, a C1 to C6 alkyl group, -C(=O)-R 4 , or -R 5 -OC(=O)-R 6 and R 4 and R 6each independently represents a substituted or unsubstituted C1 to C6 alkyl group, a C2 to C20 alkenyl group, a C2 to C20 alkynyl group, or a substituted or unsubstituted C6 to C20 aryl group, R 5 is a substituted or unsubstituted C1-C6 alkylene group, Said L 1 , L 2 , R 4 , R 5 , and R 6 The substituents are each independently deuterium, -F, -Cl, -Br, -I, -CN, -NO 2 , and -SO 3 One or more selected from the group consisting of *L 1 or L 2 At the position of binding to L 1 and L 2 If both are direct bonds, R 1 and R 2 At the same time, instead of the following CS-7, L 1 and L 2 are methylene groups and n is 2, R 1 and R 2 At the same time, it is not CS-2 as below. [ka]

[0017] (2) The present invention relates to the R 1 and R 2 are each independently selected from the group consisting of CS-1 to CS-15 below, [ka]

[0018] (3) The present invention relates to the L 1 and L 2 is a methylene group.

[0019] (4) The present invention relates to the R 1 and R 2 is independently any one selected from the group consisting of CS-1, CS-2, CS-5, CS-8, CS-10, and CS-11.

[0020] (5) The present invention provides the compound according to any one of (1) to (4) above, which is any one selected from the group consisting of the following compounds A to R: [ka] [ka] [ka]

[0021] (6) The present invention provides a non-aqueous electrolyte additive comprising the compound according to any one of (1) to (5) above.

[0022] (7) The present invention provides a non-aqueous electrolyte solution comprising a lithium salt, a non-aqueous solvent, and the non-aqueous electrolyte additive described in (6) above.

[0023] (8) The present invention provides the nonaqueous electrolyte according to (7) above, wherein the nonaqueous electrolyte additive is contained in an amount of 0.01% by weight to 10% by weight based on the total weight of the nonaqueous electrolyte.

[0024] (9) In the present invention, the lithium salt is LiCl, LiBr, LiI, LiBF 4 , LiClO 4 , LiB 10 Cl 10 , LiAlCl 4 , LiAlO 4 , LiPF 6 , LiCF 3 SO 3 , LiCH 3CO 2 , LiCF 3 CO 2 , LiAsF 6 , LiSbF 6 , LiCH 3 SO 3 , LiFSI(Lithium bis(fluorosulfonyl)imide, LiN(SO 2 F) 2 ), LiBETI(lithium bisperfluoroethanesulfonimide, LiN(SO 2 CF 2 CF 3 ) 2 ), and LiTFSI (lithium(bis)trifluoromethanesulfonimide, LiN(SO 2 CF 3 ) 2 The nonaqueous electrolyte solution according to (7) or (8) above is one or more selected from the group consisting of:

[0025] (10) The present invention provides the nonaqueous electrolyte solution according to any one of (7) to (9), wherein the nonaqueous solvent is one or more selected from the group consisting of a cyclic carbonate organic solvent, a linear carbonate organic solvent, a cyclic ester organic solvent, and a linear ester organic solvent.

[0026] (11) The present invention provides a lithium secondary battery including a positive electrode, a negative electrode, a separator, and the nonaqueous electrolyte solution according to any one of (7) to (10). Effect of the Invention

[0027] The compound of the present invention is obtained with a good synthesis yield and has good storage stability. When used as an additive for a non-aqueous electrolyte, the compound of the present invention forms a low-resistance and stable SEI, thereby improving the life of the battery and reducing the amount of gas generation, thereby improving the stability at high temperatures. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0028] The present invention will now be described in more detail.

[0029] The terms and words used in this specification and the claims should not be interpreted in a limited manner to their ordinary or dictionary meanings, but should be interpreted in a manner that is consistent with the technical idea of ​​the present invention, based on the principle that the inventors can appropriately define the concepts of terms in order to best describe their invention.

[0030] Compound represented by chemical formula 1 The present invention provides a compound represented by the following Chemical Formula 1:

[0031] [ka]

[0032] In the above Chemical Formula 1, n is 1 or 2; L 1 and L 2 are each independently a direct bond or a substituted or unsubstituted C1-C6 alkylene group, R 1 and R 2 are each independently a substituent represented by the following chemical formula 2, [ka] In the above Chemical Formula 2, m is 1 or 2; X 1 and X 2 are each independently -O- or -C(R 31 )(R 32 )-, wherein said X 1 and X 2 At least one of is -O-; R 31 ~R 36 are each independently a hydrogen atom, a C1 to C6 alkyl group, -C(=O)-R 4 , or -R 5 -OC(=O)-R6 and R 4 and R 6 each independently represents a substituted or unsubstituted C1 to C6 alkyl group, a C2 to C20 alkenyl group, a C2 to C20 alkynyl group, or a substituted or unsubstituted C6 to C20 aryl group, R 5 is a substituted or unsubstituted C1-C6 alkylene group, Said L 1 , L 2 , R 4 , R 5 , and R 6 The substituents are each independently deuterium, -F, -Cl, -Br, -I, -CN, -NO 2 , and -SO 3 One or more selected from the group consisting of *L 1 or L 2 At the position of binding to L 1 and L 2 If both are direct bonds, R 1 and R 2 At the same time, instead of the following CS-7, L 1 and L 2 are methylene groups and n is 2, R 1 and R 2 At the same time, it is not CS-2 as below. [ka]

[0033] The compound represented by Chemical Formula 1 provided by the present invention is characterized in that it contains a sulfur oxide structure in the center and has cyclic sulfur oxide structures at both ends. By adopting such a chemical structure, when it is applied as an additive to a non-aqueous electrolyte, it is possible to induce stable formation of anions in the non-aqueous electrolyte and further to form a stable SEI layer. Specifically, the compound represented by Chemical Formula 1 contains SO xBy including two or more (2≦x≦4) functional groups, the formation of the coating can be efficiently induced. Specifically, the compound represented by Chemical Formula 1 is reduced faster than the non-aqueous solvent in the electrolyte during charging and discharging, and can form a strong coating containing LiSOx (2≦x≦4) before a side reaction occurs. This minimizes an increase in interface resistance and prevents the electrode surface from being exposed, thereby suppressing side reactions between the electrode and the electrolyte. Furthermore, it is possible to effectively control the elution of transition metals from the positive electrode due to the collapse of the coating, and to realize a lithium secondary battery that has excellent high-temperature storage characteristics and high-temperature cycle characteristics while not causing battery swelling.

[0034] Meanwhile, the compound represented by the formula 1 has a reduction potential of 0.5 eV or more, which is higher than that of non-aqueous solvents, and therefore is decomposed first under cell operating conditions, forming a strong coating. The reduction potential can be measured by the following method using the Gaussian 09 program package (Gaussian 09 Revision C.01, Gaussian Inc., Wallingford, CT, 2009) that applies the DFT calculation method.

[0035] 1) Calculate the stable structural energy (Eneut) of the compound in the state before reduction and the stable structural energy (Ered) of the compound in the reduced state. 2) Eneut-Ered-1.45 eV is defined as the reduction stability value. 3) At this time, the calculation of structural stabilization is performed using the PCM (Polarizable Continuum Model) method.

[0036] More specifically, in the compound represented by the chemical formula 1 of the present invention, 1 and R 2 may each independently be selected from the group consisting of CS-1 to CS-15 below. [ka]

[0037] The structures CS-1 to CS-15 of the substituents listed above are R 1 and R 2 The substituents of CS-1 to CS-15 are preferably R 1 and R 2 When the R is applied to the non-aqueous electrolyte, the overall compound has excellent structural stability and can smoothly function as an additive for the non-aqueous electrolyte. 1 and R 2 are each independently any one selected from the group consisting of CS-1, CS-2, CS-5, CS-8, CS-10, and CS-11, from the viewpoints of structural stability and ease of synthesis.

[0038] On the other hand, in the compound represented by Chemical Formula 1 of the present invention, L 1 and L 2 are direct bonds, and R 1 and R 2 If the CS-7 is used, or if the L 1 and L 2 are both methylene groups, n is 2, and R 1 and R 2 In the case where R is CS-2 at the same time, the compound itself has low structural stability and is easily decomposed, so that the synthesis of the compound itself may be difficult. In particular, the compound satisfying the above conditions is preferably a compound in which R having a ring shape is added during the synthesis process. 1 and R 2 The structure is easily decomposed, and even if a compound is finally synthesized, it is easily decomposed during storage, and the synthesis yield is extremely low. 1 and L 2 are direct bonds, and R 1 and R 2 is CS-7, n is 2, and R 1 and R 2 Compounds where is simultaneously CS-2 are excluded.

[0039] In the compound represented by the above Chemical Formula 1, 1 and L2 may each independently be a direct bond, a methylene group or an ethylene group, and is particularly preferably a methylene group. 1 and L 2 When is a methylene group, the compound can be easily synthesized and decomposition of the compound after synthesis can be suppressed.

[0040] More specifically, the compound is particularly preferably any one selected from the group consisting of the following compounds A to R. [ka] [ka] [ka]

[0041] When the compound represented by Chemical Formula 1 has the structure described as being preferred above, it has an advantage that a stable SEI layer having low resistance can be formed even at a smaller content than that of conventionally used additives.

[0042] Non-aqueous electrolyte additive The present invention provides a non-aqueous electrolyte additive comprising the compound represented by the above-mentioned Chemical Formula 1. As described above, when the compound represented by Chemical Formula 1 is used as an additive to a non-aqueous electrolyte, a stable SEI layer can be formed, and exposure of the electrode surface can be prevented, thereby providing excellent high-temperature storage characteristics and high-temperature cycle characteristics.

[0043] The non-aqueous electrolyte additive provided by the present invention may contain other compounds known to be usable as non-aqueous electrolyte additives in addition to the compound represented by Chemical Formula 1. The specific type of other compounds contained together is not particularly limited, and any other compounds that do not inhibit the effect of the compound represented by Chemical Formula 1 and can be used as non-aqueous electrolyte additives can be used. For example, compounds that can be used together include vinylene carbonate (VC), fluoroethylene carbonate (FEC), 1,3-propane sultone (PS), ethylene sulfate (Esa), etc.

[0044] non-aqueous electrolyte The present invention provides a non-aqueous electrolyte solution comprising the above-mentioned non-aqueous electrolyte additive, a lithium salt, and a non-aqueous solvent. The non-aqueous electrolyte additive is as described above, and may be included in an amount of 0.01 wt% to 10 wt%, preferably 0.1 wt% to 8 wt%, and particularly preferably 0.5 wt% to 6 wt%, based on the total weight of the non-aqueous electrolyte solution. When the additive is included within the above range, it is possible to minimize performance degradation due to side reactions and maximize improvements in discharge stability and charge / discharge efficiency.

[0045] 1) Lithium salt The non-aqueous electrolyte of the present invention contains a lithium salt. The lithium salt is a component for providing lithium ions in the electrolyte, and any lithium salt that is generally used in non-aqueous electrolytes for lithium secondary batteries can be used without any particular limitation.

[0046] For example, Li as a cation + and as its counter ion, F - , Cl - , Br - , I - , NO 3 - , N(CN) 2 - , B.F. 4 - , ClO 4 - , B 10 Cl 10 - , AlCl4 - 、AlO 4 - 、PF 6 - 、CF 3 SO 3 - 、CH 3 CO 2 - 、CF 3 CO 2 - 、AsF 6 - 、SbF 6 - 、CH 3 SO 3 - 、(CF 3 CF 2 SO 2 ) 2 N - 、(CF 3 SO 2 ) 2 N - 、(FSO 2 ) 2 N - 、BF 2 C 2 O 4 - 、BC 4 O 8 - 、PF 4 C 2 O 4 - 、PF 2 C 4 O 8 - 、(CF 3 ) 2 PF 4 - 、(CF 3 ) 3 PF 3 - 、(CF 3 ) 4 PF 2 - 、(CF 3 ) 5 PF - 、(CF 3 ) 6 P - 、C 4 F9 SO 3 - , C.F. 3 CF 2 SO 3 - , C.F. 3 CF 2 (CF 3 ) 2 CO - , (CF 3 SO 2 ) 2 CH - , C.F. 3 (CF 2 ) 7 SO 3- , and SCN - The lithium salt may include one or more selected from the group consisting of:

[0047] More specifically, the lithium salt is LiCl, LiBr, LiI, LiBF 4 , LiClO 4 , LiB 10 Cl 10 , LiAlCl 4 , LiAlO 4 , LiPF 6 , LiCF 3 SO 3 , LiCH 3 CO 2 , LiCF 3 CO 2 , LiAsF 6 , LiSbF 6 , LiCH 3 SO 3 , LiFSI(Lithium bis(fluorosulfonyl)imide, LiN(SO 2 F) 2 ), LiBETI(lithium bisperfluoroethanesulfonimide, LiN(SO 2 CF 2 CF 3 ) 2 ), and LiTFSI (lithium(bis)trifluoromethanesulfonimide, LiN(SO 2 CF 3 ) 2) may include one or more selected from the group consisting of

[0048] The concentration of the lithium salt in the non-aqueous electrolyte can be appropriately adjusted depending on the purpose within a generally acceptable range, and may be, for example, 0.5 M to 5.0 M, specifically, 0.8 M to 4.0 M or 1.0 M to 3.0 M. If the concentration of the lithium salt is too low, the mobility of lithium ions may be poor, resulting in poor output and cycle characteristics of the lithium secondary battery, whereas if the concentration of the lithium salt is too high, the viscosity of the non-aqueous electrolyte may increase, resulting in poor impregnation of the electrolyte.

[0049] 2) Non-aqueous solvents The non-aqueous electrolyte of the present invention includes a non-aqueous solvent for dissolving the lithium salt and the additive. Specifically, the non-aqueous solvent may be one or more selected from the group consisting of a cyclic carbonate organic solvent, a linear carbonate organic solvent, a cyclic ester organic solvent, and a linear ester organic solvent, and in particular, a cyclic carbonate organic solvent, a linear carbonate organic solvent, or a mixed organic solvent thereof may be used.

[0050] The cyclic carbonate organic solvent is a high-viscosity organic solvent that has a high dielectric constant and can effectively dissociate the lithium salt in the electrolyte. Specific examples of the cyclic carbonate organic solvent include at least one organic solvent selected from the group consisting of ethylene carbonate (EC), propylene carbonate (PC), 1,2-butylene carbonate, 2,3-butylene carbonate, 1,2-pentylene carbonate, 2,3-pentylene carbonate, and vinylene carbonate, and among these, ethylene carbonate may be included.

[0051] The linear carbonate organic solvent is an organic solvent having low viscosity and low dielectric constant, and a representative example thereof may be at least one organic solvent selected from the group consisting of dimethyl carbonate (DMC), diethyl carbonate (DEC), dipropyl carbonate, ethyl methyl carbonate (EMC), methyl propyl carbonate, and ethyl propyl carbonate, and specifically may include ethyl methyl carbonate (EMC).

[0052] In addition to the cyclic carbonate organic solvent and / or linear carbonate organic solvent, at least one ester organic solvent selected from the group consisting of linear ester organic solvents and cyclic ester organic solvents may be further included in order to further increase ionic conductivity.

[0053] Specific examples of such linear ester-based organic solvents include at least one organic solvent selected from the group consisting of methyl acetate, ethyl acetate, propyl acetate, methyl propionate, ethyl propionate, propyl propionate, and butyl propionate.

[0054] The cyclic ester organic solvent may be at least one organic solvent selected from the group consisting of γ-butyrolactone, γ-valerolactone, γ-caprolactone, σ-valerolactone, and ε-caprolactone.

[0055] In addition to the above organic solvents, organic solvents that are generally used in non-aqueous electrolytes for lithium secondary batteries may be added as necessary without limitation. For example, at least one of ether-based organic solvents, amide-based organic solvents, and nitrile-based organic solvents may be further included.

[0056] 3) SEI film forming additives The nonaqueous electrolyte of the present invention may further contain an SEI-forming additive in the nonaqueous electrolyte, as necessary, in order to prevent the nonaqueous electrolyte from being decomposed in a high-output environment, which would cause the collapse of the negative electrode, or to further improve low-temperature high-rate discharge characteristics, high-temperature stability, overcharge prevention, and effects of suppressing battery expansion at high temperatures.

[0057] Representative examples of such an SEI-forming additive may include at least one SEI film-forming additive selected from the group consisting of cyclic carbonate-based compounds, halogen-substituted carbonate-based compounds, sultone-based compounds, sulfate-based compounds, phosphate-based compounds, borate-based compounds, decanenitrile, and nitrile-based compounds other than 1,4-dicyano-2-butene, benzene-based compounds, amine-based compounds, silane-based compounds, and lithium salt-based compounds.

[0058] The cyclic carbonate compound may be vinylene carbonate (VC) or vinyl ethylene carbonate, and may be contained in an amount of 3 wt% or less based on the total weight of the non-aqueous electrolyte. If the content of the cyclic carbonate compound in the electrolyte exceeds 3 wt%, the performance of suppressing cell swelling may be deteriorated.

[0059] The halogen-substituted carbonate-based compound may be fluoroethylene carbonate (FEC), which may be contained in an amount of 5 wt% or less based on the total weight of the electrolyte. If the content of the halogen-substituted carbonate-based compound in the electrolyte exceeds 5 wt%, the cell swelling performance may be deteriorated.

[0060] The sultone compound includes at least one compound selected from the group consisting of 1,3-propane sultone (PS), 1,4-butane sultone, ethene sultone, 1,3-propene sultone (PRS), 1,4-butene sultone, and 1-methyl-1,3-propene sultone.

[0061] The sultone-based compound may be included in an amount of 0.3 wt % to 5 wt %, specifically 1 wt % to 5 wt %, based on the total weight of the non-aqueous electrolyte. If the content of the sultone-based compound in the electrolyte exceeds 5 wt %, an excessively thick coating may be formed on the surface of the electrode, which may cause an increase in resistance and a decrease in output, and an excessive amount of additives in the electrolyte may increase resistance and cause a decrease in output characteristics.

[0062] The sulfate-based compound may be ethylene sulfate (Esa), trimethylene sulfate (TMS), or methyl trimethylene sulfate (MTMS), and may be contained in an amount of 5 wt % or less based on the total weight of the electrolyte.

[0063] The phosphate-based compound may be one or more compounds selected from the group consisting of lithium difluoro(bisoxalato)phosphate, lithium difluorophosphate, tetramethyltrimethylsilylphosphate, trimethylsilylphosphite, tris(2,2,2-trifluoroethyl)phosphate, and tris(trifluoroethyl)phosphite, and may be contained in an amount of 5 wt % or less based on the total weight of the electrolyte.

[0064] The borate-based compound includes tetraphenylborate and lithium oxalyl difluoroborate, and may be contained in an amount of 5% by weight or less based on the total weight of the electrolyte.

[0065] The nitrile compound is a nitrile compound other than decanenitrile (DN) and 1,4-dicyano-2-butene (DCB), and representative examples thereof include at least one compound selected from the group consisting of succinonitrile, adiponitrile, acetonitrile, propionitrile, butyronitrile, valeronitrile, caprylonitrile, heptanenitrile, cyclopentanecarbonitrile, cyclohexanecarbonitrile, 2-fluorobenzonitrile, 4-fluorobenzonitrile, difluorobenzonitrile, trifluorobenzonitrile, phenylacetonitrile, 2-fluorophenylacetonitrile, and 4-fluorophenylacetonitrile, and 1,3,6-hexanetricarbonitrile.

[0066] The content of the nitrile compound may be 5% by weight to 8% by weight, specifically 6% by weight to 8% by weight, based on the total weight of the non-aqueous electrolyte. If the content of the nitrile compound in the electrolyte exceeds 8% by weight, the resistance increases due to an increase in the coating formed on the surface of the electrode, which may result in deterioration of the battery performance.

[0067] The benzene-based compound may be fluorobenzene, the amine-based compound may be triethanolamine or ethylenediamine, and the silane-based compound may be tetravinylsilane.

[0068] The lithium salt compound is a compound different from the lithium salt contained in the nonaqueous electrolyte, and LiPO 2 F 2 , LiODFB, LiBOB (Lithium Bis(oxalato)borate (LiB(C 2 O 4 ) 2 ), and LiBF 4 and may be contained in an amount of 5 wt % or less based on the total weight of the electrolyte.

[0069] When vinylene carbonate, vinyl ethylene carbonate, succinonitrile, or the like is further contained among these SEI forming additives, a stronger SEI film can be formed on the surface of the negative electrode during the initial activation process of the secondary battery.

[0070] The LiBF 4 When the electrolyte contains the above-mentioned, generation of gas that may be generated by decomposition of the electrolyte at high temperatures can be suppressed, and the high-temperature stability of the secondary battery can be improved.

[0071] Meanwhile, the SEI forming additive may be used in a mixture of two or more kinds, and may be included in an amount of 0.1 to 50 wt%, specifically 0.01 to 10 wt%, and preferably 0.05 to 5 wt%, based on the total weight of the non-aqueous electrolyte. If the content of the SEI forming additive is less than 0.01 wt%, the effect of improving the low-temperature output of the battery, as well as the high-temperature storage characteristics and high-temperature life characteristics is small, and if the content of the SEI forming additive is more than 50 wt%, excessive side reactions may occur in the electrolyte during charging and discharging of the battery. In particular, if the SEI film forming additive is added in an excessive amount, it may not be sufficiently decomposed at high temperatures and may exist in the electrolyte at room temperature as an unreacted substance or precipitated state. This may cause a side reaction that reduces the life or resistance characteristics of the secondary battery.

[0072] Lithium secondary battery In another embodiment of the present invention, a lithium secondary battery is provided that includes the non-aqueous electrolyte of the present invention.

[0073] The lithium secondary battery provided by the present invention may be manufactured by forming an electrode assembly in which a positive electrode, a negative electrode, and a separator are sequentially stacked between the positive electrode and the negative electrode, housing the electrode assembly in a battery case, and then introducing the nonaqueous electrolyte solution of the present invention into the battery case.

[0074] The positive electrode, negative electrode, and separator included in the lithium secondary battery of the present invention can be manufactured and applied by a conventional method known in the art, specifically as described below.

[0075] 1) Positive electrode The positive electrode can be manufactured by coating a positive electrode slurry containing a positive electrode active material, a binder, a conductive material, a solvent, etc. on a positive electrode current collector, and then drying and rolling it.

[0076] The positive electrode current collector is not particularly limited as long as it does not cause a chemical change in the battery and has conductivity. For example, stainless steel, aluminum, nickel, titanium, fired carbon, or a material obtained by surface treatment with carbon, nickel, titanium, silver, etc. on the surface of aluminum or stainless steel may be used.

[0077] The positive electrode active material is a compound capable of reversible intercalation and deintercalation of lithium, and specifically, may include a lithium composite metal oxide containing one or more metals such as cobalt, manganese, nickel, or aluminum and lithium.

[0078] More specifically, the lithium composite metal oxide is a lithium-manganese-based oxide (e.g., LiMnO 2 , LiMn 2 O 4 etc.), a lithium-cobalt-based oxide (e.g., LiCoO 2 etc.), a lithium-nickel-based oxide (e.g., LiNiO 2 etc.), a lithium-nickel-manganese-based oxide (e.g., LiNi 1-Y Mn Y O 2 (0 < Y < 1), LiMn 2-z Ni z O 4 (0 < Z < 2), a lithium-nickel-cobalt-based oxide (e.g., LiNi 1-Y1 Co Y1 O 2 (0 < Y1 < 1), a lithium-manganese-cobalt-based oxide (e.g., LiCo 1-Y2 Mn Y2 O 2 (0 < Y2 < 1), LiMn 2-z1 Co z1 O 4(0 < Z1 < 2), lithium-nickel-manganese-cobalt-based oxide (e.g., Li(Ni p Co q Mn r1 )O 2 (0 < p < 1, 0 < q < 1, 0 < r1 < 1, p + q + r1 = 1) or Li(Ni p1 Co q1 Mn r2 )O 4 (0 < p1 < 2, 0 < q1 < 2, 0 < r2 < 2, p1 + q1 + r2 = 2), or lithium-nickel-cobalt-transition metal (M) oxide (e.g., Li(Ni p2 Co q2 Mn r3 M s2 )O 2 (M is selected from the group consisting of Al, Fe, V, Cr, Ti, Ta, Mg, and Mo, and p2, q2, r3, and s2 are atomic fractions of independent elements, where 0 < p2 < 1, 0 < q2 < 1, 0 < r3 < 1, 0 < s2 < 1, and p2 + q2 + r3 + s2 = 1), and any one or two or more of these compounds may be included. Among them, from the viewpoint of enhancing the cycle characteristics and stability of the battery, the lithium composite metal oxide is LiCoO 2 , LiMnO 2 , LiNiO 2 , lithium nickel manganese cobalt oxide (e.g., Li(Ni 0.6 Mn 0.2 Co 0.2 )O 2 , Li(Ni 0.5 Mn 0.3 Co 0.2 )O 2 , or Li(Ni 0.8 Mn 0.1 Co 0.1 )O 2 etc.), or lithium nickel cobalt aluminum oxide (e.g., Li(Ni 0.8 Co 0.15 Al 0.05 )O 2 etc.). Considering the remarkable improvement effect by controlling the types and content ratios of the constituent elements forming the lithium composite metal oxide, the lithium composite metal oxide is Li(Ni0.6 Mn 0.2 Co 0.2 )O 2 , Li(Ni 0.5 Mn 0.3 Co 0.2 )O 2 , Li(Ni 0.7 Mn 0.15 Co 0.15 )O 2 , or Li(Ni 0.8 Mn 0.1 Co 0.1 )O 2 etc., and any one or a mixture of two or more of these can be used.

[0079] The positive electrode active material may be included in an amount of 80 wt% to 99 wt%, specifically 90 wt% to 99 wt%, based on the total weight of the solid content in the positive electrode slurry. In this case, if the content of the positive electrode active material is 80 wt% or less, the energy density may be reduced, resulting in a reduced capacity.

[0080] The binder is a component that assists in binding the active material and conductive material and the current collector, and is usually added in an amount of 1 to 30% by weight based on the total weight of the solid content in the positive electrode slurry. Examples of such binders include polyvinylidene fluoride, polyvinyl alcohol, carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinylpyrrolidone, tetrafluoroethylene, polyethylene, polypropylene, ethylene-propylene-diene termonomer, styrene-butadiene rubber, fluororubber, various copolymers, and the like.

[0081] The conductive material is a substance that imparts conductivity to the battery without causing any chemical change, and may be added in an amount of 1 to 20% by weight based on the total weight of the solid content in the positive electrode slurry.

[0082] Representative examples of such conductive materials include carbon powders such as carbon black, acetylene black, ketjen black, channel black, furnace black, lamp black, and thermal black; graphite powders such as natural graphite, artificial graphite, and graphite with highly developed crystal structures; conductive fibers such as carbon fibers and metal fibers; conductive powders such as carbon fluoride powder, aluminum powder, and nickel powder; conductive whiskers such as zinc oxide and potassium titanate; conductive metal oxides such as titanium oxide; and conductive materials such as polyphenylene derivatives.

[0083] The solvent may also include an organic solvent such as NMP (N-methyl-2-pyrrolidone), and may be used in an amount that provides a suitable viscosity when the positive electrode active material, and optionally a binder and a conductive material, are contained. For example, the positive electrode slurry containing the positive electrode active material, and optionally a binder and a conductive material may be contained so that the solids concentration in the positive electrode slurry is 10% by weight to 60% by weight, and preferably 20% by weight to 50% by weight.

[0084] 2) Negative electrode The negative electrode may be prepared by coating a negative electrode current collector with a negative electrode slurry containing a negative electrode active material, a binder, a conductive material, a solvent, and the like, followed by drying and rolling.

[0085] The negative electrode current collector generally has a thickness of 3 to 500 μm. Such a negative electrode current collector is not particularly limited as long as it does not cause a chemical change in the battery and has high conductivity, and for example, copper, stainless steel, aluminum, nickel, titanium, baked carbon, copper or stainless steel surface treated with carbon, nickel, titanium, silver, etc., aluminum-cadmium alloy, etc. may be used. In addition, as with the positive electrode current collector, the binding force of the negative electrode active material may be strengthened by forming fine irregularities on the surface, and it may be used in various forms such as a film, sheet, foil, net, porous body, foam, nonwoven fabric, etc.

[0086] The negative electrode active material may include at least one selected from the group consisting of lithium metal, a carbon material capable of reversibly intercalating / deintercalating lithium ions, a metal or an alloy of such a metal and lithium, a metal composite oxide, a material capable of doping and dedoping lithium, and a transition metal oxide.

[0087] The carbonaceous material capable of reversibly intercalating / deintercalating lithium ions may be any carbonaceous negative electrode active material commonly used in lithium ion secondary batteries, and representative examples thereof include crystalline carbon, amorphous carbon, or a combination of both. Examples of the crystalline carbon include graphite, such as amorphous, plate-like, flake-like, spherical, or fibrous natural graphite or artificial graphite, and examples of the amorphous carbon include soft carbon (low-temperature calcined carbon), hard carbon, mesophase pitch carbide, and calcined coke.

[0088] The metal or the alloy of these metals and lithium may be a metal selected from the group consisting of Cu, Ni, Na, K, Rb, Cs, Fr, Be, Mg, Ca, Sr, Si, Sb, Pb, In, Zn, Ba, Ra, Ge, Al, and Sn, or an alloy of these metals and lithium.

[0089] The metal composite oxides include PbO, PbO 2 , Pb 2 O 3 , Pb 3 O 4 , Sb 2 O 3 , Sb 2 O 4 , Sb 2 O 5 , GeO, GeO 2 , Bi 2 O 3 , Bi 2 O 4 , Bi 2 O 5 , Lix Fe 2 O 3 (0 ≦ x ≦ 1), Li x WO 2 (0 ≦ x ≦ 1), and Sn x Me 1-x Me’ y O z (Me: Mn, Fe, Pb, Ge; Me’: Al, B, P, Si, elements of Group 1, Group 2, Group 3 of the periodic table, halogen; 0 < x ≦ 1; 1 ≦ y ≦ 3; 1 ≦ z ≦ 8) selected from the group consisting of can be used.

[0090] As substances capable of doping and undoping the lithium, Si, SiO x (0 < x ≦ 2), Si - Y alloy (wherein Y is an element selected from the group consisting of alkali metals, alkaline earth metals, Group 13 elements, Group 14 elements, transition metals, rare earth elements, and combinations thereof, and is not Si), Sn, SnO 2 , Sn - Y (wherein Y is an element selected from the group consisting of alkali metals, alkaline earth metals, Group 13 elements, Group 14 elements, transition metals, rare earth elements, and combinations thereof, and is not Sn), etc. can be mentioned, and at least one of these and SiO 2 may be mixed and used. The element Y may be selected from the group consisting of Mg, Ca, Sr, Ba, Ra, Sc, Y, Ti, Zr, Hf, Rf, V, Nb, Ta, Db, Cr, Mo, W, Sg, Tc, Re, Bh, Fe, Pb, Ru, Os, Hs, Rh, Ir, Pd, Pt, Cu, Ag, Au, Zn, Cd, B, Al, Ga, Sn, In, Ge, P, As, Sb, Bi, S, Se, Te, Po, and combinations thereof.

[0091] Examples of the transition metal oxide include lithium - containing titanium composite oxide (LTO), vanadium oxide, lithium vanadium oxide, etc.

[0092] The negative electrode active material may be contained at 80% to 99% by weight based on the total weight of the solid content in the negative electrode slurry.

[0093] The binder is a component that assists in bonding between the conductive material, the active material, and the current collector, and is usually added in an amount of 1 to 30% by weight based on the total weight of the solid content in the negative electrode slurry. Examples of such binders include polyvinylidene fluoride, polyvinyl alcohol, carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinylpyrrolidone, tetrafluoroethylene, polyethylene, polypropylene, ethylene-propylene-diene monomer, styrene-butadiene rubber, fluororubber, and various copolymers thereof.

[0094] The conductive material is a component for further improving the conductivity of the negative electrode active material, and may be added in an amount of 1 to 20% by weight based on the total weight of the solid content in the negative electrode slurry. Such a conductive material is not particularly limited as long as it does not cause a chemical change in the battery and has conductivity, and may be, for example, carbon powder such as carbon black, acetylene black, ketjen black, channel black, furnace black, lamp black, or thermal black; graphite powder such as natural graphite, artificial graphite, or graphite with a highly developed crystal structure; conductive fibers such as carbon fibers and metal fibers; conductive powders such as carbon fluoride powder, aluminum powder, and nickel powder; conductive whiskers such as zinc oxide and potassium titanate; conductive metal oxides such as titanium oxide; conductive materials such as polyphenylene derivatives, etc.

[0095] The solvent may include water or an organic solvent such as NMP or alcohol, and may be used in an amount that provides a suitable viscosity when the negative electrode active material and, optionally, a binder and a conductive material are contained therein. For example, the solvent may be contained so that the concentration of solids in the slurry containing the negative electrode active material and, optionally, a binder and a conductive material is 50% by weight to 75% by weight, preferably 50% by weight to 65% by weight.

[0096] 3) Separator The separator included in the lithium secondary battery of the present invention may be a commonly used conventional porous polymer film, for example, a porous polymer film made of a polyolefin polymer such as an ethylene homopolymer, a propylene homopolymer, an ethylene / butene copolymer, an ethylene / hexene copolymer, or an ethylene / methacrylate copolymer, either alone or in a laminated state, or a conventional porous nonwoven fabric, for example, a nonwoven fabric made of a high melting point glass fiber, a polyethylene terephthalate fiber, or the like, but is not limited thereto.

[0097] The external shape of the lithium secondary battery of the present invention is not particularly limited, and may be a cylindrical shape using a can, a square shape, a pouch shape, a coin shape, or the like.

[0098] Hereinafter, the present invention will be described in detail with reference to examples in order to specifically explain the present invention. However, the examples of the present invention can be modified into various other forms, and the scope of the present invention should not be interpreted as being limited to the examples described below. The examples of the present invention are provided to more completely explain the present invention to those having average knowledge in the art.

[0099] Synthesis Example Each compound was synthesized by the following method.

[0100] 1) Synthesis of Compound B In a flask, add 5 g of 3-butene-1,2-diol, Na 2 S 2 O 5 The reaction solution was concentrated by distillation under reduced pressure, and 50 mL of methanol was added to obtain a precipitate. The precipitate was filtered under reduced pressure and dried in a vacuum oven to obtain 10 g of sodium 3,4-dihydroxybutane sulfonate.

[0101] Then, 10g of dried sodium 3,4-dihydroxybutanesulfonate, 0.2g of DMF, and 70g of THF were added to a flask, and 10g of thionyl chloride was slowly added dropwise at 0°C. After the addition was completed, the reactant was heated at 60°C for 2 hours, and then cooled to room temperature, and HCl and MeOH were added. The reactant was then passed through a silica column and concentrated under reduced pressure to obtain 5g of 3-hydroxymethyl-1,3-propane sultone.

[0102] Next, 30 g of ethyl acetate and 3 g of pyridine were placed in a flask, and 2.2 g of thionyl chloride was slowly added at 0°C. After stirring at room temperature for 30 minutes, 5 g of the 3-hydroxymethyl-1,3-propane sultone obtained above was dissolved in 20 g of ethyl acetate and slowly added. After reacting for 2 hours, the product was extracted as an organic layer using water and methylene chloride, and the extracted organic layer was concentrated to obtain bis((2,2-dioxido-1,2-oxathiolan-5-yl)methyl)sulfite (Compound B below).

[0103] [ka]

[0104] The synthesis or non-synthesis of the compound is 1 This was confirmed by H-NMR. 1 H-NMR(500MHz, Bruker, ACN-d3) = 4.9(2H), 4.28(2H), 4.15(2H), 3.35(4H), 2.6(2H), 2.4(2H)

[0105] 2) Synthesis of compound A 5 g of the compound B obtained by drying under reduced pressure in the above Synthesis Example 1), 40 g of acetonitrile, and 20 g of water were placed in a flask. Then, RuCl dissolved in 30 g of water at 0° C.3 0.03g and NaIO 4 After 30 minutes of reaction, 100 g of t-butyl ether was added and stirred, and the organic layer was separated and extracted with water and ethyl acetate. After extraction, the organic layer was concentrated under reduced pressure to obtain bis((2,2-dioxido-1,2-oxathiolan-5-yl)methyl)sulfate (Compound A shown below).

[0106] [ka]

[0107] The synthesis or non-synthesis of the compound is 1 This was confirmed by H-NMR. 1 H-NMR(500MHz, Bruker, ACN-d3) = 5.1(2H), 4.7(2H), 4.6(2H), 3.5(4H), 2.9(2H), 2.4(2H)

[0108] 3) Synthesis of compound C 5g of moisture-controlled glycerol and 90g of dimethyl carbonate (DMC) were added to a flask, and then 13g of thionyl chloride was slowly added dropwise at 0°C. After the reaction was completed, the reaction solvent and the generated HCl were all removed by distillation under reduced pressure, and 90g of dimethyl carbonate was further added. Then, 8.3g of 3-hydroxymethyl-1,3-propane sultone prepared in Synthesis Example 1) was dissolved in 10g of dimethyl carbonate, and then slowly added dropwise at 0°C. After the reaction for 3 hours, the mixture was extracted with water and ethyl acetate, and then the organic layer was dried under reduced pressure to obtain ((2,2-dioxido-1,2-oxathiolan-5-yl)methyl)((2-oxide-1,3,2-dioxathiolan-4-yl)methyl)sulfite (compound C shown below).

[0109] [ka]

[0110] The compound C has a characteristic that it exists in a form in which stereoisomers are mixed in a molar ratio of 6:4 due to a cyclic sulfite structure, and the synthesis or non-synthesis of the compound is 1 This was confirmed by H-NMR. 1 H-NMR (500MHz, Bruker, CDCl 3 ) = 5.1(0.6H), 4.9(1H), 4.8(1H), 4.6(0.6H), 4.4~4.0(4.8H), 3.3(2H), 2.7(1H), 2.5(1H)

[0111] 4) Synthesis of compound G 2 g of glycerol with controlled moisture and 40 g of dimethyl carbonate (DMC) were added to the flask, and then 2.7 g of thionyl chloride was slowly added dropwise at 0°C. After the reaction was completed, the reaction solvent and the generated HCl were all removed by distillation under reduced pressure, and 40 g of acetonitrile and 30 g of water were further added. Then, RuCl dissolved in 20 g of water at 0°C was added. 3 0.5g and NaIO 4 After 30 minutes of reaction, 100g of t-butyl ether was added and stirred, and the organic layer was separated and extracted with water and ethyl acetate. After extraction, the organic layer was concentrated under reduced pressure to obtain 4-(hydroxymethyl)-1,3,2-dioxathiolane 2,2-dioxide. 10g of dimethyl carbonate was placed in a flask, 1.5g of thionyl chloride was slowly added, and 2g of the 4-(hydroxymethyl)-1,3,2-dioxathiolane 2,2-dioxide obtained above was slowly added at 0°C. After 1 hour, 2g of 3-hydroxymethyl-1,3-propane sultone dissolved in 5g of dimethyl carbonate was slowly added at 0°C. After the reaction was allowed to proceed for 3 hours, 50g of methylene chloride (MC) and water were added to extract the organic layer. MgSO 4 After removing water from the organic layer using a filter, the organic layer was dried under reduced pressure to obtain (2,2-dioxido-1,2-oxathiolan-5-yl)methyl((2,2-dioxido-1,3,2-dioxathiolan-4-yl)methyl)sulfite (2,2-dioxido-1,2-oxatholan-5-yl)methyl((2,2-dioxido-1,3,2-dioxathiolan-4-yl)methyl)sulife, compound G shown below).

[0112] [ka]

[0113] The synthesis or non-synthesis of the compound is 1 This was confirmed by H-NMR. 1 H-NMR(500MHz, Bruker, ACN-d3) = 5.3(1H), 5.1(1H), 4.9(2H), 4.4~4.1(2H), 3.87(1H), 3.75(1H), 3.4~3.2(2H), 2.65(1H), 2.4(1H)

[0114] 5) Synthesis of compound H Into a flask, 2g of glycerol with controlled moisture and 40g of dimethyl carbonate (DMC) were added, and then 2.6g of thionyl chloride was slowly dropped at 0°C. After the reaction was completed, the reaction solvent and the generated HCl were all removed by vacuum distillation, and 3g of 4-(hydroxymethyl)-1,3,2-dioxathiolane 2-oxide was obtained. Into another flask, 2g of glycerol with controlled moisture and 20g of dimethyl carbonate (DMC) were added, and then 5.2g of thionyl chloride was slowly dropped at 0°C. After the reaction was completed, the reaction solvent and the generated HCl were all removed by vacuum distillation, and 30g of dimethyl carbonate was further added. Then, 3g of 4-(hydroxymethyl)-1,3,2-dioxathiolane 2-oxide prepared above was dissolved in 10g of dimethyl carbonate and slowly added at 0°C. After the reaction for 3 hours, the mixture was extracted with water and ethyl acetate, and the organic layer was dried under reduced pressure to obtain bis((2-oxido-1,3,2-dioxathiolan-4-yl)methyl)sulfite (Compound H below).

[0115] [ka]

[0116] The compound H has a characteristic that it exists in a form in which stereoisomers are mixed in a molar ratio of 6:4 due to a cyclic sulfite structure, and the synthesis of the compound is 1 This was confirmed by H-NMR. 1H-NMR (500MHz, Bruker, CDCl 3 ) = 5.15(1.2H), 4.78(2H), 4.6(1.2H), 4.4(2.8H), 4.2~4.0(2.8H)

[0117] 6) Synthesis of Compound I 2 g of glycerol with controlled moisture and 40 g of dimethyl carbonate (DMC) were added to the flask, and then 2.7 g of thionyl chloride was slowly added dropwise at 0°C. After the reaction was completed, the reaction solvent and the generated HCl were all removed by distillation under reduced pressure, and 40 g of acetonitrile and 30 g of water were further added. Then, RuCl dissolved in 20 g of water at 0°C was added. 3 0.5g and NaIO 4 After 30 minutes of reaction, 100g of t-butyl ether was added and stirred, and the organic layer was separated and extracted with water and ethyl acetate. After extraction, the organic layer was concentrated under reduced pressure to obtain 4-(hydroxymethyl)-1,3,2-dioxathiolane 2,2-dioxide. 10g of dimethyl carbonate was placed in a flask, 1.5g of thionyl chloride was slowly added, and 2g of the 4-(hydroxymethyl)-1,3,2-dioxathiolane 2,2-dioxide obtained above was slowly added at 0°C. After the reaction was carried out for 2 hours, 50g of methylene chloride (MC) and water were added to extract the organic layer. MgSO 4 After removing water from the organic layer using a filter, the organic layer was dried under reduced pressure to obtain bis((2,2-dioxido-1,3,2-dioxathiolan-4-yl)methyl)sulfite (Compound I shown below).

[0118] [ka]

[0119] The synthesis or non-synthesis of the compound is1 This was confirmed by H-NMR. 1 H-NMR(500MHz, Bruker, ACN-d3) = 5.3(2H), 4.9~4.8(4H), 3.8(4H)

[0120] 7) Synthesis of compound X (Comparative synthesis example) In a flask, add 50 g of 3-chloro-1,2-propanediol and Na 2 SO 360g of sodium 2,3-dihydroxypropane sulfonate and 200mL of water were added and heated and stirred at 65℃ for 7 hours. The solution was concentrated by distillation under reduced pressure, and then 300mL of methanol was added to generate a precipitate. The precipitate was filtered under reduced pressure, washed with methanol, and dried in vacuum to obtain sodium 2,3-dihydroxypropane sulfonate. 30g of dried sodium 2,3-dihydroxypropane sulfonate, 0.5g of DMF, and 75mL of toluene were added to a flask, and 48g of thionyl chloride was slowly added dropwise at room temperature. After the addition was completed, the reaction mixture was heated at 65℃ for 5 hours. After the heating was completed, the reaction mixture was cooled to room temperature, and 50mL of MeOH was added and stirred for 3 hours. The reaction mixture was reduced pressure to remove the remaining solvent, and then passed through a silica gel column to obtain 2-hydroxy-1,3-propane sultone. 1g of the prepared 2-hydroxy-1,3-propane sultone was dissolved in 4mL of acetonitrile, and 0.6g of pyridine and 0.9g of thionyl chloride were slowly added dropwise at 0℃, followed by reaction at room temperature for 1 hour. Then, 1g of 2-hydroxy-1,3-propane sultone was slowly added dropwise together with 0.6g of pyridine, followed by stirring for 2 hours. After the reaction was completed, the organic layer extracted with ethyl acetate was concentrated. However, the content of decomposition products generated during the reaction was high in this process, and compound X was obtained in a yield of less than 40% in the concentrated solution extracted with ethyl acetate, and the decomposition products were not completely removed in the aqueous layer, so further separation was performed using a silica column (mobile phase (eluent): a mixture of ethyl acetate and hexane in a weight ratio of 2:1). Further separation using the silica column was completed to obtain bis(2,2-dioxido-1,2-oxathiolan-4-yl)sulfite (Compound X shown below). The final yield of Compound X was about 20%.

[0121] [ka]

[0122] The synthesis or non-synthesis of the compound is 1 This was confirmed by H-NMR. 1 H-NMR(500MHz, Bruker, ACN-d3) = 5.0(1H), 4.7(1H), 4.5(1H), 3.8(1H), 3.5(1H)

[0123] 8) Synthesis of compound Y (Comparative synthesis example) 3 g of the compound X obtained by drying under reduced pressure in the above Synthesis Example 7), 20 g of acetonitrile, and 12 g of water were placed in a flask. Then, RuCl dissolved in 15 g of water at 0° C. 3 0.02g and NaIO 4 2.5g of ethyl acetate was slowly added dropwise while stirring. After 30 minutes of reaction, 50g of ethyl acetate was added and stirred, and the organic layer was separated and extracted with water and acetyl acetate. After extraction, the organic layer was concentrated under reduced pressure to obtain bis(2,2-dioxido-1,2-oxathiolan-4-yl)sulfate (compound Y below). However, due to the decomposition products generated in the above process, it was confirmed that the purity of compound Y was very low.

[0124] In order to obtain the compound Y with higher purity, sulfuryl chloride was used instead of thionyl chloride for 1 g of 2-hydroxy-1,3-propane sultone prepared in Synthesis Example 7) above, and the same process as in Synthesis Example 7) was carried out to obtain the compound Y. However, even by this method, the compound Y was obtained in a yield of about 20%.

[0125] [ka]

[0126] The synthesis or non-synthesis of the compound is 1 This was confirmed by H-NMR. 1 H-NMR(500MHz, Bruker, ACN-d3) = 5.5(2H), 5.3(2H), 5.1(2H), 3.9(2H), 3.8(2H)

[0127] 9) Synthesis of compound Z (Comparative synthesis example) 5 g of the compound H obtained by drying under reduced pressure in the above Synthesis Example 5), 38 g of acetonitrile, and 19 g of water were placed in a flask. Then, RuCl dissolved in 28 g of water at 0° C. 3 0.025g and NaIO 4 The mixture was stirred while slowly adding 3.5g of t-butyl ether dropwise. After 30 minutes of reaction, 90g of t-butyl ether was added and stirred, and the organic layer was separated and extracted with water and ethyl acetate. However, bis((2,2-dioxido-1,3,2-dioxathiolan-4-yl)methyl)sulfate (compound Z below), which is sensitive to moisture, was completely decomposed and could not be obtained.

[0128] Therefore, as another synthesis method, sulfuryl chloride was used instead of thionyl chloride for 2 g of 4-(hydroxymethyl)-1,3,2-dioxathiolane 2,2-dioxide produced in the above Synthesis Example 6) to obtain compound Z through a process similar to that of Synthesis Example 6). However, even with this method, compound Z was obtained in a yield of about 10%.

[0129] [ka]

[0130] The synthesis or non-synthesis of the compound is 1 This was confirmed by H-NMR. 1 H-NMR(500MHz, Bruker, ACN-d3) = 5.4(2H), 4.95~4.8(4H), 4.6(4H)

[0131] Examples and Comparative Examples LiPF was dissolved in a non-aqueous solvent consisting of ethylene carbonate and ethyl methyl carbonate in a volume ratio of 3:7. 6 After dissolving the compound in the above Synthesis Example to a concentration of 1.0 M, 99 g of the solution was taken. 1 g of the compound synthesized in the above Synthesis Example or a conventional additive was added to the solution to prepare a non-aqueous electrolyte.

[0132] Furthermore, the positive electrode active material (lithium nickel-cobalt-manganese oxide (Li(Ni 0.8 Co 0.1 Mn 0.1 )O 2 ), conductive material (carbon black), and binder (polyvinylidene fluoride) were mixed in a weight ratio of 97.5:1:1.5, and then added to N-methyl-2-pyrrolidone (NMP) to prepare a positive electrode slurry (solid content 60% by weight). The positive electrode slurry was applied to a positive electrode current collector (Al thin film) with a thickness of 15 μm, and then dried and roll pressed to prepare a positive electrode. Separately, a negative electrode active material (artificial graphite), conductive material (carbon black), and binder (polyvinylidene fluoride) were mixed in a weight ratio of 96:0.5:3.5, and then added to N-methyl-2-pyrrolidone (NMP) to prepare a negative electrode slurry (solid content 50% by weight). The negative electrode slurry was applied to a negative electrode current collector (Cu thin film) with a thickness of 8 μm, and then dried and roll pressed to prepare a negative electrode. Then, the produced positive electrode, inorganic particles (Al 2 O 3 The electrode assembly was then stored in a pouch-shaped battery case, and the non-aqueous electrolyte for lithium secondary batteries prepared above was poured into the pouch-shaped battery case, thereby producing a pouch-shaped lithium secondary battery.

[0133] The types and contents of additives used in the batteries prepared in the Examples and Comparative Examples are summarized in Table 1 below.

[0134] [Table 1]

[0135] Experimental example 1. Evaluation of high-temperature cycle characteristics of batteries The batteries prepared in the examples and comparative examples were activated at a constant current (CC) of 0.1C. Then, at 25°C, using a PESC05-0.5 charger / discharger (manufacturer: PNE Solution Co., Ltd., 5V, 500Ma), they were charged at 0.33C CC to 4.2V under constant current-constant voltage (CC-CV) charging conditions, and then discharged at 0.33C to 2.5V under constant current conditions after a current cut of 0.05C. The above charge / discharge cycle was counted as one cycle, and two cycles were performed. Then, the batteries were fully charged at a constant current-constant voltage of 0.33C / 4.2V, and discharged at 2.5C for 10 seconds at SOC50%, and the voltage before and after discharge were measured, and the initial resistance was calculated using the voltage difference before and after the discharge. Next, the battery was discharged at a constant current of 0.33C until it reached 2.5V, and then degassed. The battery was charged at a constant current of 0.33C until it reached 4.2V within the voltage driving range of 2.5V to 4.2V under the condition of 45°C, and then charged at a constant voltage of 4.2V until it reached 4.2V. When the charging current reached 0.05C, the charging was terminated. After that, the battery was left for 20 minutes, and then discharged at a constant current of 0.33C until it reached 2.5V. The above charging and discharging constituted one cycle, and 100 cycles of charging and discharging were repeated.

[0136] At this time, the capacity after the first cycle and the capacity after the 100th cycle were measured using a PESC05-0.5 charger / discharger, and the capacity was substituted into the following [Equation 1] to calculate the capacity retention rate.

[0137] [Formula 1] Capacity retention rate (%) = (Capacity after 100 cycles / Capacity after 1 cycle) x 100

[0138] After 100 cycles, the battery was discharged at 2.5C for 10 seconds at SOC 50%, and the voltage before and after discharge was measured, and the resistance after 100 cycles was calculated using the voltage difference before and after discharge. The resistance increase rate was calculated by substituting the initial resistance calculated above and the resistance after 100 cycles into the following [Equation 2].

[0139] [Formula 2] Resistance increase rate (%) = {(resistance after 100 cycles - initial resistance) / initial resistance} x 100

[0140] The capacity retention rate and resistance increase rate calculated for the batteries of each of the examples and comparative examples are summarized in Table 2 below.

[0141] [Table 2]

[0142] As shown in the results of Table 2 above, it can be confirmed that Examples 1 to 6, which used the nonaqueous electrolyte additive of the present invention, have higher capacity retention rates and lower resistance increase rates, and thus have excellent cycle characteristics, compared to Comparative Example 1, which did not use any additive. Furthermore, Comparative Examples 2 and 3, which used a conventional nonaqueous electrolyte additive instead of the additive of the present invention, also showed lower capacity retention rates and higher resistance increase rates than the Examples of the present invention, confirming that a battery with particularly excellent cycle characteristics can be manufactured when the nonaqueous electrolyte additive of the present invention is used.

[0143] In addition, the compounds X, Y, and Z, which have a similar structure to the compounds of the present invention but are not included in the scope of the present invention, were used as non-aqueous electrolyte additives in Comparative Examples 4 to 6, which showed slightly inferior capacity retention and resistance increase rates compared to the Examples of the present invention. As described in the Synthesis Examples section, the compounds X, Y, and Z have drawbacks in the synthesis process, such as being difficult to synthesize or being decomposed after synthesis completion, resulting in a very low yield, and are not superior to the compounds of the present invention in terms of performance. Therefore, it can be confirmed that the compounds of the present invention are more suitable for use as non-aqueous electrolyte additives than the compounds X, Y, and Z.

[0144] Experimental example 2: Evaluation of high-temperature storage characteristics of batteries The volume change rate and resistance increase rate after high-temperature storage of the batteries manufactured in the examples and comparative examples were measured by the following methods.

[0145] 1) Volume change rate (%) After activating each battery at a constant current of 0.1C, it was charged at a constant current of 0.33C to 4.2V at 25°C using a PESC05-0.5 charger / discharger under constant current-constant voltage charging conditions, and then discharged at 0.33C to 2.5V under constant current conditions after cutting the current at 0.05C. The above charge / discharge cycle was considered as one cycle, and two cycles were performed. Next, the battery was fully charged at a constant current-constant voltage of 0.33C / 4.2V, and discharged at 2.5C for 10 seconds at SOC50%, and the voltage before and after discharge were measured, and the initial resistance was calculated using the voltage difference before and after the discharge. Next, the battery was discharged at a constant current of 0.33C to 2.5V, and then degassed. The battery charged and discharged above was placed in a bowl filled with water at room temperature using a TWD-150DM device (manufacturer: Two-pls), and the initial volume was measured. The battery was then fully charged at a constant current-constant voltage of 0.33C / 4.2V and stored at 60°C for 4 weeks (SOC 100%), and the volume after high-temperature storage was measured in the same manner using the TWD-150DM device. The measured initial volume and the volume after high-temperature storage were substituted into the following [Equation 3] to calculate the volume change rate.

[0146] [Formula 3] Volume change rate (%) = {(volume after high-temperature storage - initial volume) / initial volume} x 100

[0147] 2) Resistance increase rate (%) The initial resistance was measured according to the above process, and the battery was discharged to 2.5 V at a constant current of 0.33 C, degassed, and charged to 4.2 V. The battery was then stored at 60° C. for 4 weeks (SOC 100%), and then further discharged at 2.5 C for 10 seconds at SOC 50%, and the resistance after high-temperature storage was measured. The initial resistance value and the resistance value after high-temperature storage measured as above were substituted into the following [Equation 4] to calculate the resistance increase rate.

[0148] [Formula 4] Resistance increase rate (%) = {(resistance value after high temperature storage - initial resistance value) / initial resistance value} x 100

[0149] The volume change rate and resistance increase rate calculated for each battery using the above-mentioned method are summarized in Table 3 below.

[0150] [Table 3]

[0151] As shown in Table 3 above, it was confirmed that the batteries of the examples have less gas generation, less volume change, and less increase in resistance even after high-temperature storage compared to the batteries of Comparative Examples 1 to 3, and therefore can stably maintain capacity characteristics.

[0152] In addition, the batteries of Comparative Examples 4 to 6 showed similar performance to those of the Examples under high-temperature storage conditions. However, as explained in Experimental Example 1 above, they have disadvantages in terms of synthesis and storage, and also have disadvantages in terms of cycle characteristics that are inferior to those of the Examples.

Claims

1. A non-aqueous electrolyte additive comprising a compound represented by the following chemical formula 1: 【Chemistry 1】 (In the above Chemical Formula 1, n is 1 or 2; L 1 and L 2 is a methylene group, R 1 and R 2 are each independently any one selected from the group consisting of CS-1, CS-2, CS-5, CS-8, CS-10, and CS-11; When n is 2, R 1 and R 2 At the same time, it is not CS-2 as described below. 【Chemistry 2】

2. The non-aqueous electrolyte additive according to claim 1 , wherein the compound is any one selected from the group consisting of the following compounds A to R: 【Chemistry 3A】 【Chemistry 3B】 【Chemistry 3C】

3. A lithium salt; A non-aqueous solvent; A non-aqueous electrolyte comprising the non-aqueous electrolyte additive according to claim 1.

4. The non-aqueous electrolyte according to claim 3, wherein the non-aqueous electrolyte additive is contained in an amount of 0.01% by weight to 10% by weight based on the total weight of the non-aqueous electrolyte.

5. The lithium salts are LiCl, LiBr, LiI, and LiBF. 4 , LiClO 4 , LiB 10 C 10 , LiAlCl 4 , LiAlO 4 , LiPF 6 , LiCF 3 SO 3 , LiCH 3 CO 2 , LiCF 3 CO 2 , LiAsF 6 , LiSbF 6 , LiCH 3 SO 3 , LiFSI (Lithium bis(fluorosulfonyl)imide, LiN(SO 2 F) 2 ), LiBETI (lithium bisperfluoroethanesulfonimide, LiN(SO 2 CF 2 CF 3 ) 2 ), and LiTFSI (lithium (bis) trifluoromethanesulfonimide, LiN(SO 2 CF 3 ) 2 5. The nonaqueous electrolyte according to claim 3, wherein the nonaqueous electrolyte is one or more selected from the group consisting of:

6. 6. The nonaqueous electrolyte solution according to claim 3, wherein the nonaqueous solvent is at least one selected from the group consisting of a cyclic carbonate organic solvent, a linear carbonate organic solvent, a cyclic ester organic solvent, and a linear ester organic solvent.

7. A positive electrode and A negative electrode; A separator; A lithium secondary battery comprising the nonaqueous electrolyte solution according to claim 3 .

Citation Information

Patent Citations

  • Nonaqueous electrolyte solution for battery, and lithium secondary battery

    JP2018156761A

  • Additive for non-aqueous electrolyte, non-aqueous electrolyte and power storage device

    JP2019179638A

  • Non-Aqueous Electrolyte for Lithium Ion Battery and Lithium Ion Battery

    US20200313237A1

  • Cyclic sulfate compound, non-aqueous electrolyte solution containing same, and lithium secondary battery

    WO2012053644A1

  • Non-aqueous electrolytic solution, electrical storage device utilizing same, and cyclic sulfonic acid ester compound

    WO2012147818A1